Mengukuhkan Peran Perempuan Sebagai Agen Perubahan Melalui Kreasi Ecoprint di Desa Candisari - Tania Elsa Rahayu; Dilla Agustiani; Anindya Ardiansari (Lembaga Pengembangan Kinerja Dosen, 2024)
Improving the economy of a community can be seen from the point of view of its environment, where each individual can take advantage of the natural potential around them. Ecoprinting is a business opportunity that can be applied by the community, especially residents of Candisari Village, Magelang Regency, which is known as an area with a city of a million flowers. This has the potential to support the creation of ecoprints by the community. This article is intended as the main means to connect the Candisari Village community with the wider community and large business owners who may be interested in ecoprint business opportunities in the area. Using the demonstration method, we first introduced eco-printing to PKK mothers to get a clear understanding of the concept, purpose and technology of eco-printing, and then practised eco-printing. This socialisation helped improve the PKK women's knowledge and skills in ecoprint batik production using textile media.